Case Report Endovascular single-chamber pacemaker implantation using active fixation in a 8 years old Dogue de Bordeaux with presumed Persistent Atrial Standstill: the first case documented in Romania - Florin Leca; Stefan Adrian Geanta; Mihaela Claudia Bolintineanu; Eusebiu Ionut Condurachi; Alina Nechifor; Daniel Barsan; Florica Bărbuceanu; Nicu Caplea; Diana Caraza (Cluj Veterinary Journal)
Background: Symptomatic bradyarrhythmias in dogs can lead to sever hemodynamical compromise due to impaired oxygen and nutrients delivery and even sudden cardiac death. In cases refractory to medical therapy the heart rate and therefore the cardiac output are maintained in physiological ranges using artificial external, internal and temporary (emergency situations) or internal and permanent cardiac pacing.